A comparison of grid-level residential electricity demand scenarios in Japan for 2050. (15th November 2015) - Yamagata, Yoshiki; Murakami, Daisuke; Seya, Hajime
Highlights: Electricity demand scenarios for Japan at 1 km 2 grid level for the year 2050 were created. Several electricity projection models were compared. It is shown that different projection methods may produce different spatial patterns. The usefulness of model ensemble for projection purposes is shown. Abstract: Scenarios of future population at the grid level (e.g., 1 km 2 ) is very important for various types of regional planning, including energy planning. Though the most often used method for population projection is the so-called cohort-component method, if our focus is world level, not country or finer level, we must rely on much simpler methods. In this study, we compare the performance of several typical simple population projection methods using the residential electricity demand derived from each population scenario, especially focusing on spatial patterns. We show that different projection methods may produce different spatial patterns such as "compact" or "dispersed" urban form, which is quantified using the Gini coefficient. Also, we show that the projection method for gravity-based residential electricity demand is very flexible in that it can create the most compact and the most dispersed urban form among the focused methods. Furthermore, we point out the usefulness of model ensemble in projection.